2013
DOI: 10.1089/ten.tea.2012.0281
|View full text |Cite
|
Sign up to set email alerts
|

Stromal Cell Identity Influences the In Vivo Functionality of Engineered Capillary Networks Formed by Co-delivery of Endothelial Cells and Stromal Cells

Abstract: A major translational challenge in the fields of therapeutic angiogenesis and tissue engineering is the ability to form functional networks of blood vessels. Cell-based strategies to promote neovascularization have been widely explored, and have led to the consensus that co-delivery of endothelial cells (ECs) (or their progenitors) with some sort of a supporting stromal cell type is the most effective approach. However, the choice of stromal cells has varied widely across studies, and their impact on the funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
53
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 49 publications
7
53
1
Order By: Relevance
“…In this model, we have previously demonstrated that MSC cotransplantation with ECs yields less permeable and more mature vessels than those formed from EC transplantation alone. 20,21 In the present study, fluorescent staining showed more dextran contained within the vessels where either MSCs or PDLSCs were cotransplanted, relative to the condition where only ECs were tranplanted (Fig. 5A).…”
Section: Fig 4 Pdlsc Effect On In Vivosupporting
confidence: 51%
See 1 more Smart Citation
“…In this model, we have previously demonstrated that MSC cotransplantation with ECs yields less permeable and more mature vessels than those formed from EC transplantation alone. 20,21 In the present study, fluorescent staining showed more dextran contained within the vessels where either MSCs or PDLSCs were cotransplanted, relative to the condition where only ECs were tranplanted (Fig. 5A).…”
Section: Fig 4 Pdlsc Effect On In Vivosupporting
confidence: 51%
“…19 Therefore, a 70-kDa Texas Red-conjugated dextran (k ex/em of 595/615 nm; Invitrogen) was chosen as a functionally defining tracer as described previously. 20,21 This dextran molecule contains free lysines, which are fixable in 4% paraformaldehyde (PFA). Before implant retrieval, mice were placed in a restraint device and 100 mL of a 5 mg/mL dextran solution in PBS was then injected through the tail vein.…”
Section: In Vivo Angiogenic Potential Of Pdlscsmentioning
confidence: 99%
“…In a subsequent in vivo study it is planned to compare both subsets of cells with respect to capillary formation and wound healing to support the hypothesis of this article. It has been shown that MSCs derived from different sources regulate angiogenesis via distinct mechanisms and that their identity also influences the functional properties of in vivo vessel implants [69,70]. In our study, we investigated MSCs isolated from a perivascular as well as an avascular niche, and could show that both have angiogenic properties.…”
Section: Discussionmentioning
confidence: 91%
“…22 After sedation as previously described, mice were imaged in triplicate. A region of interest was drawn over the implant area and the mean perfusion through each implant was calculated.…”
Section: Laser Doppler Perfusion Imagingmentioning
confidence: 99%